Handbook of proteases in cancer : cellular and molecular aspects - Chakraborti, Sajal (Boca Raton, FL. : CRC Press, 2025)
"This handbook provides comprehensive coverage of the role of proteases and the associated biochemical pathways in cancer development and metastasis. Proteases make up to about two percent of the human genome and play a critical role in the tumor microenvironment. The book introduces the major classes of proteases and the signal transduction mechanisms associated with cancer initiation and progression. It discusses the role of inflammation and immune responses in proteases-induced cancer. The book covers cancer-induced gene expression and apoptotic and necrotic pathways in cancer. The text is useful for researchers and professionals in cancer research, biochemistry, and physiology"--
Includes bibliographical references and index.
Keywords: Neoplasms -- etiology; Neoplasms -- genetics; Peptide Hydrolases -- physiology